2016
DOI: 10.1007/s00239-016-9740-1
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Model for the Evolution of Protein Structure

Abstract: Protein domains are three-dimensional arrangements of atomic structure that are recurrent in the proteomes of organisms. Since the three-dimensional structure of a protein determines its function, it is the fold, much more than the underlying protein sequence and underlying chemistry, that is evolutionarily conserved. We are interested in probing the history of life with these domain structures and glimpsing qualitative changes over time by studying a dynamic model of protein evolution. Using standard phylogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…We fitted the models to data from ToDs assuming that only transitions present in the trees were possible between fold structures and that branches emerged directly from a trunk. We found that parameters of growth of domains within FSFs (FSF reuse) and diversification of FSFs (FSF use) showed emergent biphasic patterns with opposing trends, i.e., increases in FSF innovation were always counterbalanced by decreases in growth of FSF abundance, and vice versa, with the growth of the many more recent FSFs offsetting the growth of the older FSFs (Tal et al, 2016). Since the model is global and independent of the existence of proteomes, simulations suggest a frustrated and complex interplay of growth and diversification of domain structures in the protein world that emerges from organismal diversification but is not a consequence of proteome size.…”
Section: Fsf Setmentioning
confidence: 91%
See 1 more Smart Citation
“…We fitted the models to data from ToDs assuming that only transitions present in the trees were possible between fold structures and that branches emerged directly from a trunk. We found that parameters of growth of domains within FSFs (FSF reuse) and diversification of FSFs (FSF use) showed emergent biphasic patterns with opposing trends, i.e., increases in FSF innovation were always counterbalanced by decreases in growth of FSF abundance, and vice versa, with the growth of the many more recent FSFs offsetting the growth of the older FSFs (Tal et al, 2016). Since the model is global and independent of the existence of proteomes, simulations suggest a frustrated and complex interplay of growth and diversification of domain structures in the protein world that emerges from organismal diversification but is not a consequence of proteome size.…”
Section: Fsf Setmentioning
confidence: 91%
“…While there are a number of Heaps-like scaling relationships in the vocabulary of genomes that appear universal, some reflecting the scaling of number of genes in different functional categories as a function of genome size (Molina and van Nimwegen, 2009), the link between dynamic and static properties of the models must always be confirmed with phylogenetic methods. We recently built global dynamic models for the evolution of structural domains that used birth-death differential equations with global abundances of domains as state variables without the need to capture the distribution of domains in proteomes (Tal et al, 2016). We fitted the models to data from ToDs assuming that only transitions present in the trees were possible between fold structures and that branches emerged directly from a trunk.…”
Section: Fsf Setmentioning
confidence: 99%
“…These escape routes allowed cells to begin to evolve toward miniaturisation, further evolving the process that had led to the formation of chromosomes, now grouping together genes with common functional associations and co-transcribing them together as operons [81]. These processes would be reflected in a stepwise evolution of the structure of proteins, as indeed observed by Caetano-Anollés and co-workers [82]. …”
Section: Reviewmentioning
confidence: 99%
“…While the first appearance of these innovations are rare events, their retention and loss in trees of these highly conserved features is a durable and relatively common phenomenon. We have made the distinction between innovation and innovation spread explicit in a dynamic model of proteome evolution, which we found explains the phylogenomics of the CA 2 characters (Tal et al 2016 ). The model uses global birth–death differential equations and domain abundances as state values and is governed by two parameter classes, λ j or the rate (birth minus death) of generating new variants of a same domain structure j , and a ij or the rate of ‘forward’ transition from structure j to structure i .…”
Section: Resultsmentioning
confidence: 91%
“…It could be argued, however, that stepmatrix models could be tested and improved by a mathematical approximation to more realistic statistical models, using, for example, fitted model and time parameters inferred from an evolutionary model of proteome evolution (e.g. a dynamic birth–death model; Tal et al 2016 ) or probabilities informed by stepmatrices obtained from CSR. Indeed, the HK model has been parametrized for Bayesian reconstruction from binary characters of FSF occurrence (Harish and Kurland 2017b ) using the nonstationary model developed by Klopfstein et al ( 2015 ).…”
Section: Resultsmentioning
confidence: 99%